MORPHOLOGICAL FEATURES OF POPLITEAL LYMPH NODES IN WHITE OUTBRED RATS WITH RHEUMATOID ARTHRITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The study investigates age-dependent histochemical and morphometric changes in peripheral lymph nodes of white outbred rats with experimental rheumatoid arthritis. Alsian blue staining revealed reactive-proliferative and reparative processes in young (3-month-old) rats, moderate compensatory activity in middle-aged (12-month-old) rats, and predominance of fibrotic and involutional changes in older (18-month-old) rats. Age-related accumulation of glycosaminoglycans in stroma, trabeculae, and sinus walls reflects chronic inflammation and tissue remodeling. The findings highlight dynamic structural and functional adaptations of lymph nodes in autoimmune pathology, providing insights into immunoregulatory mechanisms and potential therapeutic interventions.